Pengaruh Financial Reporting Quality,Internet Financial Reporting (IFR) dan Transparency Terhadap Information Asymmetry - Selmha Bella Arvhiari; Dirvi Surya Abbas; Mohamad Zulman Hakim (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
This study aims to examine the effect of Financial Reporting Quality, Internet Financial Reporting and Transparency variables on Information Asymmetry. This research is a quantitative study that uses secondary data. The population in this study are infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period, totaling 56 companies. The results of this study indicate that Financial Reporting Quality has no effect on Information Asymmetry, Internet Financial Reporting has no effect on Information Asymmetry, Transparency has a negative effect on Information Asymmetry.